2019
DOI: 10.18203/2320-1770.ijrcog20190295
|View full text |Cite
|
Sign up to set email alerts
|

Use of non-pneumatic anti shock garment in hemorrhagic shock

Abstract: Background: Non-pneumatic anti-shock garment (NASG) is a first-aid device that reverses hypovolemic shock and decreases obstetric haemorrhage. It consists of articulated neoprene segments that close tightly with Velcro, shunting blood from the lower body to the core organs, elevating blood pressure and increasing preload and cardiac output. The use of an NASG can stabilize a patient while awaiting transport, during transport, or during delays in receiving care at referral facilities.Methods: A prospective obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Escobar M F et al in 2017 found that while 52% patients were primi, remaining 48% were multipara and grandmultipara [9]. One more study by Bangal VB et al in 2019 observed that 84% patients were multipara and grandmultipara [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Escobar M F et al in 2017 found that while 52% patients were primi, remaining 48% were multipara and grandmultipara [9]. One more study by Bangal VB et al in 2019 observed that 84% patients were multipara and grandmultipara [10].…”
Section: Discussionmentioning
confidence: 99%
“…[8] Another study by Escobar M F et al in 2017 studied that major etiology was uterine atony (96%), retained products /placenta (15%), vaginal tears(6%), placenta praevia (5%). (9) A study by Bangal VB et al in 2019 observed that atonic PPH occurred in 77.7% of patients while remaining had traumatic PPH [10].…”
Section: Original Research Articlementioning
confidence: 98%
See 3 more Smart Citations